The Role of Theater of the Oppressed on Correction and Rehabilitation of Prisoners (Case Study: Yazd Province Prisons) - Jabbari, Mehrdad; Dadvar, Abolghasem (Journal of History Culture and Art Research, 2018)
Nowadays attention to the function of theater in various social domains is considered by artists, sociologists and psychologists. Among the various types of theater functions, educational work and behavior modification in the form of theatrical theater and theater therapy in Iran are more than welcome. The audience of this type of theater is mostly those who feel the need to change their behavior, lifestyle, and thought. But due to the limitations of the performance of this show, such as the creation of appropriate text, the effective and efficient application space of artists in this way of communicating effectively, some social groups have less use of this type of display. The prisoners' group is less likely to participate in this way than the rest of the groups, given the special security and protection requirements. On the other hand, the prisoners' problems require that, along with the usual methods of rehabilitation and improvement of education, new and more effective methods be used and their effects published. Therefore, the functioning in prisons, which has so far been neglected, should be investigated in a scientific and analytical manner. The statistical population of this research includes 135 prisoners in Yazd province. The research results show that theater is effective in reforming prisoners.